1993
DOI: 10.1257/jep.7.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Does Studying Economics Inhibit Cooperation?

Abstract: F rom the perspective of many economists, motives other than self-interest are peripheral to the main thrust of human endeavor, and we indulge them at our peril. In Gordon Tullock's (1976) words (as quoted by Mansbridge, 1990, p. 12), "the average human being is about 95 percent selfish in the narrow sense of the term."In this paper we investigate whether exposure to the self-interest model commonly used in economics alters the extent to which people behave in self-interested ways. The paper is organized into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
626
12
24

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,231 publications
(715 citation statements)
references
References 5 publications
33
626
12
24
Order By: Relevance
“…Even high-quality education that includes training in formal methods and critical thinking can have problematic effects. For instance, several studies indicate that the study of economics makes students on average more selfish than they were before (Frank et al 1993;Rubinstein 2005). [Higher education may also increase the risk of becoming a professor or university don-a profession characterized by E. Friedell as involving ''a slow metabolism, a sluggish bowel, a penchant for gradualist doctrines, and pedantry'' (Kolnai 1976).…”
Section: Safetymentioning
confidence: 99%
“…Even high-quality education that includes training in formal methods and critical thinking can have problematic effects. For instance, several studies indicate that the study of economics makes students on average more selfish than they were before (Frank et al 1993;Rubinstein 2005). [Higher education may also increase the risk of becoming a professor or university don-a profession characterized by E. Friedell as involving ''a slow metabolism, a sluggish bowel, a penchant for gradualist doctrines, and pedantry'' (Kolnai 1976).…”
Section: Safetymentioning
confidence: 99%
“…There is evidence from laboratory experiments that economics and business students behave more selfishly than other people (Frank et al, 1993;Frank and Schulze, 2000), but also that the major does not matter with respect to selfish behavior (Frey and Meier, 2002). Moreover, men have been shown to hold slightly more optimistic self-efficacy beliefs than women (Wilson et al, 2007).…”
Section: --------------------------------Figure 3 -------------------mentioning
confidence: 99%
“…The bulk of experimental research has revealed that competitive strategies are preferred in such ''one-shot''-settings, at least in nations with an individualistic cultural tradition (Boone & van Witteloostuijn, 1999). The baseline strategy, however, also depends on the players' educational background: economics students, for instance, tend to compete much more often than their colleagues studying other majors (Frank, Gilovich, & Regan, 1993). In the second game, we manipulated the reputation of the other (fictitious) party by suggesting that this party was trustworthy because (s)he had made cooperative choices in each of the 12 rounds in the previous encounter (i.e.…”
Section: Gamesmentioning
confidence: 99%